Effects of COVID-19 restrictions on mechanization service providers and mechanization equipment retailers: Insights from phone surveys in Myanmar - Takeshima, Hiroyuki; Masias, Ian; Win, Myat Thida; Zone, Phoo Pye (Wiley, 2023)
Agrifood sector mechanization service providers (MSP) and mechanization equipment retailers (MER) have increasingly become the providers of mechanical technologies for smallholders in developing countries, including Myanmar. Evidence remains scarce on the effects of COVID‐19 on these MSPs and MERs. This study provides insights into the effects of COVID‐19 restrictions on MSPs and MERs in Myanmar, using unbalanced panel data from five rounds of phone surveys. Direct responses to COVID‐19 involving movement restrictions, market disruptions, and growing financial challenges had significant negative effects on revenue prospects, service delivery, and sales of machines and equipment. Negative revenue prospects during a particular period can further hurt revenue prospects in subsequent periods. This is consistent with the hypotheses that MSPs who had incurred high sunk costs in machines can engage in more desperate and, thus, potentially suboptimal business practices to recover the sunk cost. Overall, policies to minimize movement restrictions and various financial struggles and mitigate any pessimism at the beginning of the production season are all important to make sure MSPs and MERs continue to function effectively under COVID‐19.